PERAN ORANG CINA DALAM PEREKONOMIAN KESULTANAN ISLAM BANTEN ABAD XVI-XVIII - Siti Fauziah (Al Qalam, 2009)
The Chinese people play a great role in the World economy, especially in Indonesia, both in the past and at present. From the sixteenth century to the eighteenth century, as the revival period of Muslim trade signed by the growth of the emporiums in several Islamic kingdom areas, Chinese traders gave a large contribution to the economic development, especially in the Banten Sultanate at the time. The great work ethos of Chinese has caused them, successful in dominating business in many countries.The existence of Chinese people in Banten in the past was much different from that of European people who came into Banten to colonize and to arise the economic and political tensions in the Banten sultanate. In the Sultanate period, the Chinese people played a significant role not only in the trading sector of Banten, but also in its monetary sector so that they had a great influence to the socio-economic changes in Banten. The Chinese traders in Banten was considered by Dutch as a serious threat for Dutch trade in Banten. However, the Chinese skill and their social status in the community were frequently made use of by Dutch people for their own trade interest.